Sex selection in Islamic perspective - Haneef, Sayed Sikandar Shah (Oxford University Press, 2018)
Sex selection, which refers to any fertility technology or technique that attempts to control the gender of a child, has changed the traditional landscape in human reproduction. The questions associated with this choice have made it a topic for heated debate among ethicists. The most important ethical question that it raises from a religious perspective is that it infringes upon God`s authority over sex formation of the embryo. This entry therefore attempts to examine the Islamic juridico-ethical position on sex selection technology.